Metody podnoszenia efektywności procesów w polskich przedsiębiorstwach - ograniczenia i kierunki zmian - Cyfert, Szymon (Methods of Process Improvement Applied in Polish Enterprises - Limitations and Directions of Developing, 2009)
The aim of this article is to discuss the results of research into the limitations on process improvement methods applied in Polish enterprises. The article starts with a description of methodology of research. This helps the author present the research results and derive the final conclusion concerning limitations on process improvement methods applied in Polish enterprises. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 162-169